Cardiac Death due to Cardiomyophaties in Forensic Autopsies - Karayel, Ferah; Turan, Arzu Akçay; Pakiş, Işıl; Akyıldız, Elif Ülker; Ersoy, Gökhan; Yılmaz, Eyüp (The Bulletin of Legal Medicine, 2006)
Cardiomyopathy is a group of myocardial muscle disease of unknown origin. Primary ones consist of dilated, hypertrophic, obliterative and ARVC subgroups. The aim of this study is to describe macroscopic and microscopic features of this pathologic entity that is a rare cause of death among young adult population. Eleven cases of cardiomyopathy were detected in autopsy population of the Council of Forensic Medicine between 2003 and 2006. Of these cases, 5 were male and 6 were female and age range was 15-35. After histopathologic examination of these cardiomyopathy cases, seven were detected to be hypertrophic, three dilated and one restrictive cardiomyopathy resulting from amyloid accumulation. No toxic substances were detected on routine toxicological analysis. The cause of death in these 11 sudden death cases was reported to be cardiac death resulting from cardiomyopathy. In order to support the legal investigation process in sudden deaths, it is crucial to establish the cause of death. Detailed macroscopic and microscopic examination of heart must be performed in order to detect cardiomyopathies during investigating the sudden death of young adults.Key words: Autopsy, cardiac sudden death, cardiomyopathy
Keywords: autopsy; cardiac sudden death; cardiomyopathy